An injectable robust denatured albumin hydrogel formed via double equilibrium reactions. Issue 8 (24th May 2019) - Bai, Yu; Li, Sidi; Li, Xueping; Han, Xing; Li, Yang; Zhao, Jin; Zhang, Juntao; Hou, Xin; Yuan, Xubo
Abstract: Proteins are ideal raw materials for preparing biomaterials with better biocompatibility and larger elastic range than synthetic polymers. Injectable hydrogels are highly desired for minimal invasive strategies. At present, preparation of injectable hydrogels with good comprehensive properties using natural materials receives more and more attention. In this article, BSA was treated with urea and glutathione to prepare bovine serum albumin hydrogel controlled by two dynamic equilibrium bonds (disulfide and hydrogen bonds). The hydrogen bond equilibrium between urea-protein and protein-protein as well as the exchange reaction equilibrium between thiol-disulfide bonds in the system not only facilitated to enhance the mechanical properties, but also to reduce the gelation time to 5 min. Moreover, this novel albumin hydrogel was proved to be of good biocompatibility. Therefore, the albumin hydrogels in this article were injectable within the physiological range and shown low cytotoxicity, good machanical property ( storage modulus could be greater than 10 kPa and compressive stress could reach 0.2 MPa) and good injectability, which exhibited promising prospect.